Fluorescent Turn-off Probe of Ni2+ Based Nitrogen-Doped Carbon Dots - Kamali, SIti Raudhatul; Chen, Chang-Nan; Agrawal, Dinesh Chandra; Wei, Tai-Huei (Universitas Jenderal Soedirman, 2024)
ABSTRACT: An effective and facile method of generating nitrogen-doped carbon dots (N-CD) by microwave irradiation is presented in this study. A precursor, succinic acid (SA), and a nitrogen source, bis-(3-aminopropyl)-amine (BAPA), were used to obtain N-CD. A precious quantum yield (QY) of 49.0% was obtained from the preparation of N-CD, which was well-soluble in water. The N-CD material was highly selective and sensitive for the detection of nickel ion (Ni2+), with a detection limit of 0.26 μM and a linear concentration range of 5-175 μM. The quenching of the N-CD by the presence of Ni2+ was referred to formation of complexes because of the interaction of Ni2+ on the N-CD. Hence, the proposed study has great promise regarding Ni2+ detection in broad applications. Keywords: Microwave, Ni2+, nitrogen-doped carbon dots.